Method for Analysis and Classification of Pavement Based on Quality - David G. Asatryan; Hakobyan, Gurgen H. (Изд-во НАН РА)
The main objective of automated systems for pavement quality control is the detection of cracks and other surface defects, as well as the analysis of their corresponding parameters. On pavement areas the quality assessment is performed based on video surveys, followed by image processing with the corresponding mathematical methods.
Keywords: Mathematics; Science; Analysis